Controlling the crystalline phase of TiO2 powders obtained by the solution combustion method and their photocatalysis activity. Issue 9 (November 2015) - Ma, Xiao; Xue, Lihong; Li, Xiangbo; Yang, Miao; Yan, Youwei
Abstract: Nanocrystalline TiO2 catalysts with different anatase/rutile ratios have been successfully prepared using a single-step solution combustion synthesis (SCS). The synthesized powders were characterized using XRD, Raman, XPS, FT-IR, SEM, TEM, BET and UV–vis DRS. The effects of urea-to-nitrate molar ratio on the phase structure, morphology and photocatalytic activity of the TiO2 powders were investigated. Results show that the urea contents play an important role in controlling the crystal structure of the samples. Specifically, well-dispersed anatase/rutile TiO2 nanocomposites (anatase 66.2%, rutile 33.8%) with excellent photocatalytic activity can be obtained when the molar ratio of urea-to-nitrate is 0.50. The synergistic effect between the anatase and rutile is responsible for the enhanced performance of this material. Moreover, a thermodynamic calculation was performed to interpret the phase transformation mechanism during the combustion process.